(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is devoted to phraseology and the linguistic analysis of phraseological units, which is significant in linguistics and cultural studies. The major topic of the article, which is a linguistic and cultural analysis of the numerical components of phraseological units, greatly aids in recognizing the variations and similarities in phraseology between Uzbek and English.